Biochemical Studies of Two Bacillus pumilus Plasmids - Lovett, Paul S. (1974)
Bacillus pumilus NRS 576 harbored an estimated two copies per chromosome of a covalently closed, circular (CCC) deoxyribonucleic acid (DNA) molecule, the 576 plasmid. The 576 plasmid has a buoyant density of 1.698 g/cm(3) and a molecular weight of about 28 × 10(6). Plasmid copy number remained about the same in both exponentially growing and stationary-phase cells. Spontaneous variants of NRS 576 that formed spores at an elevated frequency were designated as W mutants. W mutants appeared to have lost the 576 plasmid on the basis of the following: W mutants (38 tested) lacked detectable CCC DNA, and the majority of the plasmid homologous sequences in bulk NRS 576 DNA were absent from bulk W mutant DNA. B. pumilus ATCC 7065 harbored at least 10 copies per chromosome of a CCC DNA element, the 7065 plasmid. The 7065 plasmid has a buoyant density of 1.696 g/cm(3) and a molecular weight of about 6 × 10(6). Although the copy number of the plasmid appeared to remain the same in exponentially growing and stationary-phase cells, an additional CCC form of higher molecular weight was detected in stationary-phase cells.